Distribution of neuropsychiatric profiles and comorbid diseases in dementia subtypes - Bülbül, Nazlı Gamze; Karşıdağ, Sibel; Çınar, Nilgün; Ateş, Miruna Florentina; Şahin, Şevki; Karalı, Fenise Selin; Gönül Öner, Özge; Okluoğlu, Tuğba; Eren, Fettah; Yılmaz Okuyan, Dilek; Totuk, Özlem; Karacan Gölen, Meltem; et al. (The European Research Journal, 2024)
Objectives: Alzheimer’s disease (AH) is the most prevalent cause of dementia, followed closely by vascular dementia. Mixed vascular-Alzheimer’s dementia (MVAD) is more evident in individuals aged 80 and above. Frontotemporal dementia (FTD) is the second most common cause of early-onset dementia after AH. Vascular risk factors play important role in the pathogenesis of dementia syndromes. Behavioral and psychological symptoms represent a significant portion of the non-cognitive manifestations in dementia patients. This study aimed to evaluate the distribution of chronic diseases, behavioral disorders, psychiatric findings, and medication use in patients followed with different dementia diagnoses. Methods: Prevalance of chronic diseases, behavioral disorders, psychiatric findings as well as the usage of antidepressant and antipsychotic medications among patients followed up in dementia outpatient clinics with the diagnosis of AD, mild cognitive impairment (MCI), vascular dementia (VaD), FTD, and MVAD were investigated. Neuropsychiatric inventory (NPI) was applied to the patients. Results: Four hundred and fifty-five patients were accepted in the study. The patients were distributed as follows: AD (n=303, female/male: 187/115, age = 78±8 years), MCI (n=53, female/male: 31/22, age = 69±10 years), VaD (n=31, female/male: 18/13, age = 68±9 years), FTD (n=32, female/male: 17/15, age = 68±9 years), and MVAD (n=36, female/male: 16/20, age = 76±10 years). Both AD and MVAD groups were significantly older than the other groups (F = 23.2, P